FAKTOR-FAKTOR YANG MEMPENGARUHI UNDERPRICING PADA PENAWARAN UMUM SAHAM PERDANA - Purbarangga, Ade; Afri Yuyetta, Etna Nur (Diponegoro Journal of Accounting, 2013)
This study aim to examine the variables that influence the level of underpricing oninitial public offering. The variables examined include auditor reputation, firm size, firmage, return on equity, and the precentage of offers moderated by market capitalization andtotal liabilities. The research was carried out by multiple regression analysis. Datacollection tools used were observational studies and literature study with purposivesampling method. Sample of 91 companies from a population of 132 companies. Theresearch concluded that first auditor reputation not proven effect on the level ofunderpricing, second firm size not proven effect on the level of underpricing, third firm agenot proven effect on the level of underpricing, fourth return on equity not proven effect onthe level of underpricing, and fifth the precentage of offers not proven effect on the level ofunderpricing.